Prognostic value of site-specific extra-hepatic disease in hepatocellular carcinoma: a SEER database analysis - Oweira, Hani; Mehrabi, Arianeb (Expert review of gastroenterology & hepatology, 2017)
Background: We the prognostic value of site-specific extra-hepatic disease in hepatocellular carcinoma (HCC) patients registered within the surveillance, epidemiology and end results (SEER) database.Methods: SEER database (2010-2013) has been queried through SEER*Stat program to determine the prognosis of advanced HCC patients according to the site of extra-hepatic disease. Survival analysis has been conducted through Kaplan Meier analysis.Results: A total of 4396 patients with stage IV HCC were identified in the period from 2010-2013 and they were included into this analysis. Patients with isolated regional lymph node involvement have better outcomes compared to patients with any other site of extra-hepatic disease (P < 0.0001 for both endpoints). Among patients with distant metastases, patients with bone metastases have better outcomes compared to patients with lung metastases (P < 0.0001 for both endpoints). Multivariate analysis revealed that younger age, normal alpha fetoprotein, single site of extra-hepatic disease, local treatment to the primary tumor and surgery to the metastatic disease were associated with better overall survival and liver cancer-specific survival.Conclusion: Within the limits of the current SEER analysis, HCC patients with isolated lung metastases seem to have worse outcomes compared to patients with isolated bone or regional nodal metastases.​
Gesehen am 30.04.2018